Institutionalizing Bugis Makassar Local Wisdom in Islamic Religious Education Curriculum at Indonesian Islamic Higher Education - Efendy, Rustan; Hamdanah, Hamdanah; Mahrusah, Luthfiyah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study formulates a theoretical model based on field experience to integrate Bugis Makassar local wisdom into Islamic Religious Education (PAI) at IAIN Parepare. Although international literature highlights the importance of culturally relevant pedagogy, the integration of local cultural values in PAI is still fragmentary, dependent on lecturers, and not yet sufficiently institutionalized. Using a qualitative design based on principles of theory grounded in field experience, data were collected through in-depth interviews with IAIN Parepare Islamic Religious Education lecturers, curriculum managers, and students, supported by classroom observations and analysis of curriculum documents and Semester Learning Plans. Data analysis used constant comparison methods through open, axial, and selective coding repeatedly. Open coding identified concepts that emerged from empirical data. Axial coding mapped the relationships between conditions, practices, and consequences, while selective coding integrated core categories into an explanatory framework verified through cross-case comparisons. The findings reveal three interconnected processes: context recognition, which acknowledges siri’, pacce, getteng, and lempu’ as ethical capital in line with Islamic principles. Its pedagogical application, operationalized through contextual pedagogy, culture-based assignments, local narratives, role models, and institutional reconfiguration, ensures sustainability through policy alignment and academic culture strengthening. Systemic integration enhances curriculum relevance while reinforcing students' religious and cultural identities.